Diagnosis of Endometrial Tuberculosis in Two Women who Underwent Assisted Reproductive Treatment for Bilateral Tubal Factor Infertility: Case Report (Annals of Medical Research, 2021)
None
Keywords: Genital Tuberculosis; Infertility; Tubal Factor; Assisted Reproductive Treatment (ART).